Impact of long-acting contraceptives on female genital tract cytokine profiles in a randomised controlled trial - Radzey, Nina (Division of Medical Virology, 2021)
The Evidence for Contraceptive Options and HIV Outcomes (ECHO) trial found no substantial difference in HIV acquisition risk between women randomised to injectable depot medroxyprogesterone acetate (DMPA-IM), copper intrauterine device (IUD) or the levonorgestrel (LNG) implant. However, it remains unknown whether these contraceptives increase HIV risk relative to other forms of contraception or no contraception. This study investigated the impact of DMPA-IM, copper IUD and LNG implant on cervicovaginal inflammatory profiles previously associated with HIV acquisition, among a sub-cohort of ECHO participants. This study included 167 ECHO participants at the Setshaba Research Centre in Pretoria and MatCH Research Unit in Durban, South Africa. Eleven cytokines and antimicrobial peptides were measured in lateral vaginal wall swabs in duplicate using Luminex. Differences in baseline cytokine profiles were assessed using demographic data, including site, age, body mass index (BMI) and sexually transmitted infection (STI) status. Changes in cytokine concentrations were assessed using Wilcoxon signed ank test. Fold changes in cytokine concentrations were compared between arms using Mann-Whitney U test. P-values were adjusted for multiple comparisons using a false discovery rate procedure. Overall cytokine profiles were compared using principal components analysis and unsupervised hierarchical clustering. Mixed effects linear regression was used for longitudinal analysis and multinomial logistic regression was used to adjust for potential confounders that were assessed at baseline. Concentrations of IL-6 and MIP-3α were significantly higher in women enrolled at the Setshaba Research Centre compared to the MatCH Research Unit. Several immune mediators were elevated in younger women and this trend was significant for the pro-inflammatory IL1β and the chemokines IL-8 and MIP-1α. Women that were seropositive for herpes simplex virus type 2 (HSV-2) had significantly lowerconcentrations of MIP-1α. The copper IUD and LNG implant were associated with rapid increases in inflammatory markers following contraceptive initiation. Pro-inflammatory IL-1β and IL-6 and chemotactic IL-8, IP-10, MIP1⍺ and MIP-1β were significantly elevated one month following copper IUD insertion. No changes were evident at one-month post LNG implant insertion, however at three months, TNF-⍺, IP-10, MIP-3⍺ and SLPI were significantly raised relative to baseline. No significant changes in immune mediator concentrations were detected following DMPA-IM initiation but the trend was towards a decrease, particularly for SLPI. After adjusting for potential confounders, including site, age and infection status with chlamydia, gonorrhoea and HSV-2, IL-6 and IP-10 were significantly elevated in the copper IUD compared to the DMPA-IM arm at months 1 and 3, while IP-10 and SLPI were higher in the LNG implant arm at month 3 compared to the DMPA-IM arm. The copper IUD and the LNG implant are associated with increased cervicovaginal inflammatory markers that have been linked to HIV infection risk and the chemokine IP-10 appears to play a central role. Recent studies have demonstrated the importance of the interplay between inflammation, the microbiome, contraception and HIV risk. Continued research to understand these effects are critical for safe contraceptive use and to inform novel contraceptive development.